Annual incidence of persistent proteinuria in the general population from Ibaraki annual urinalysis study - Nagai, Kei; Saito, Chie; Watanabe, Fumiyo; Ohkubo, Reiko; Sato, Chihiro; Kawamura, Tetsuya; Uchida, Kensuke; Hiwatashi, Akira; Kai, Hirayasu; Ishida, Kumiko; Sairenchi, Toshimi; Yamagata, Kunihiro (Clinical and experimental nephrology, 2013)
Background For a definitive diagnosis of chronic kidney disease, at least 2 consecutive positive results of proteinuria with an interval of >3 months are required. However, most previous reports were based on single-screening data. Patients and methods The subjects in this study were participants in an annual health examination held in Ibaraki, Japan, between 1993 and 2003. The follow-up duration with serial urinalysis for 3 years of patients who were negative for proteinuria in the initial year was 330,614 person-years in males and 687,381 person-years in females among 81,854 male and 155,256 female subjects. We evaluated the incidence and risk factor for the incidence of proteinuria and persistent proteinuria. Result The annual incidence of proteinuria and persistent proteinuria was 1.31 and 0.33 % in males and 0.68 and 0.14 % in females. Among the subjects without hypertension and diabetes, the annual incidence was 0.81 and 0.16 % in males and 0.37 and 0.06 % in females, respectively. Risk analysis indicated that hypertension in males [hazard ratio (HR) 2.052] and females (2.477), diabetes in males (3.532) and females (3.534) and reduced renal function in males (3.097) and females (2.827) were significant positive risks for development of persistent proteinuria. Conclusion By annual urinalysis screening of the general population, 1 out of 303 male subjects and 1 out of 725 female subjects developed persistent proteinuria every year. Subjects with diabetes, hypertension and reduced renal function had a 2 or 3 times higher risk for the incidence of persistent proteinuria in both males and females.